STRUGGLE FOR LIFE OF ROBINSON CRUSOE IN GEORGE MILLER AND RODNEY K. HARDY'S ROBINSON CRUSOE (1997): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - KURNIAWAN , EDI (2011)
The problem of this study is to reveal how the struggle of life in major character is. The objectives of the study are to analyze the major character in Robinson Crusoe movie based on Individual Psychological Approach. The study is a literary study, which can be categorized into a descriptive qualitative study. The object of this study is Robinson Crusoe movie. The data sources are primary and secondary data sources. The primary data source is the movie Robinson Crusoe script and the secondary data are related to the primary data that support the analysis such as some books of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive analysis. Based on the analysis, the writer concludes that the problem faced by the major character is struggle to go out of his condition, it causes the writer to use individual psychological perspective such as: Inferiority Feeling, Striving for Superiority, Fictional Finalism, Style of Life, Social Interest, Creative Power. By using this method, it is known how Robinson Crusoe as the major character can solve his problem.